Ten Questions on Indoor Greening and Environmental Quality - Kumar, Prashant; Sun, Hao; Biswal, Akash; Dwivedi, Anubhav Kumar; Cheung, Ho Yin Wickson; Bhui, Kamaldeep; Blanusa, Tijana; Blocken, Bert; van den Bogerd, Nicole; Calautit, John Kaiser; Carslaw, Nicola; Considine, Brian; et al. (Elsevier, 2026)
While outdoor urban greening is recognised for its benefits, indoor green infrastructure (iGI) in shaping indoor environmental quality (IEQ) - including air quality, thermal comfort, and bioaerosols - remains underexplored. This ten-question paper identifies key challenges, opportunities, and research gaps in the iGI-IEQ nexus, organised under 10 questions across five thematic clusters: (1) biophysical and technical performance; (2) ecological and microbiological dynamics; (3) human health and wellbeing; (4) equity, access, and socio-economic factors; and (5) implementation and systems integration. Findings indicate that iGI can improve air quality, regulate humidity, and enhance thermal comfort. However, its performance depends strongly on plant density, species selection, and ventilation. Most evidence comes from controlled settings. iGI may offer positive psychological and cognitive benefits, and can reduce health inequalities through affordable indoor interventions. However, significant data scarcity exists for long-term field studies, indoor microbial ecosystem effects, and socio-economic accessibility. Widespread adoption of iGI requires quantification of proven benefit conditions, followed by overcoming technical, operational, and regulatory barriers via adaptive design, digital monitoring, and interdisciplinary collaboration. As a culminating synthesis, this study introduces a newly developed comprehensive matrix that classifies twenty-six indoor greening types across twenty IEQ parameters, incorporating an assessment of current data confidence. This matrix lays a foundational framework for informed decision-making and design guidance. This review offers evidence-based insights for researchers, policymakers, and practitioners to effectively leverage iGI where suitable, in creating healthier, climate-resilient residential and commercial buildings, addressing both immediate IEQ challenges and supporting long-term sustainability objectives.
Keywords: 3301 Architecture; Social Determinants of Health; Behavioral and Social Science; Health Disparities; Health Disparities and Racial or Ethnic Minority Health Research; Generic health relevance; Building & Construction; 33 Built environment and design; 40 Engineering; Indoor green infrastructure (iGI); Indoor greening; Sustainable Living; Climate resilience; Sustainable Development Goals; Indoor environmental quality